The uncertainty of the U.S and Japanese interest rates and its effect on money demand in Malaysia - Dahalan, Jauhari (Universiti Utara Malaysia, 2004)
This paper examines the efect of the volatility of the U.S. and Japanese interest rates on the money demand in Malaysia. The volatility of the U.S. andJapanese interest rates measured as a conditional variance are estimated from the GARCH(1,1) model. The long-term relationship between real money demand in Malaysia and the volatility of the U.S., and between real money demand in Malaysia and Japanese interest rates are investigated by applying the Johansen multivariate cointegration test. Results show that the volatility of the U.S. and Japanese interest rates impose a significant influence in money demand in Malaysia. However, the opportunity cost of holding money remains to impose a larger efect on the money demand function.